2014
DOI: 10.3109/00498254.2014.915359
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolite profiling of fimasartan, a novel antihypertensive agent, in rats

Abstract: 1. The objectives of this study were to evaluate the pharmacokinetics and metabolism of fimasartan in rats. 2. Unlabeled fimasartan or radiolabeled [(14)C]fimasartan was dosed by intravenous injection or oral administration to rats. Concentrations of unlabeled fimasartan in the biological samples were determined by a validated LC/MS/MS assay. Total radioactivity was quantified by liquid scintillation counting and the radioactivity associated with the metabolites was analyzed by using the radiochemical detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…A recent preclinical study (16) indicated that fimasartan is mainly excreted via feces; and multiple peaks in the plasma concentration-time profiles were observed both after oral and IV administration, suggesting the presence of EHC. Multiple plasma concentration peaks were also present after oral administration of fimasartan in clinical trials (17)(18)(19)(20)(21)(22), indicating that EHC impacts on human PK and potentially pharmacodynamics (PD).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent preclinical study (16) indicated that fimasartan is mainly excreted via feces; and multiple peaks in the plasma concentration-time profiles were observed both after oral and IV administration, suggesting the presence of EHC. Multiple plasma concentration peaks were also present after oral administration of fimasartan in clinical trials (17)(18)(19)(20)(21)(22), indicating that EHC impacts on human PK and potentially pharmacodynamics (PD).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The rat (16) and human (21) data have been published previously, and the dog data were generated in the present study and are presented for the first time. The data sets included in our modeling analysis are summarized in the supplement Table S1.…”
Section: Data Setsmentioning
confidence: 99%
See 3 more Smart Citations